Development of Evidence-based Nursing Practice Guidelines for Peripheral Intravenous Catheter Management in Hospitalized Children (International Journal of Studies in Nursing, 2018)
Aims: The purpose of this study was to report on the development of evidence-based practice guidelines. Design: Developmental research for practice guidelines. Methods: The guidelines developmental process was designed according to a procedure provided by Scottish Intercollegiate Guidelines Network (SIGN). A first step, key clinical questions were selected. Next, 74 studies were selected from studies of 719 according to a search strategy, and then methodological quality of those studies was evaluated using assessment tool of SIGN. After the evaluation of draft guidelines including recommendations and their grades, the contents were modified. Last, definitive guidelines were evaluated using Appraisal of Guidelines for Research and Evaluation (AGREE) tool. Result: The guidelines consist of three categories and 64 recommendations, i.e. nine recommendations for user before peripheral intravenous catheterization (PIVC), 26 recommendations during PIVC, and 29 recommendations after PIVC. Content validity was revealed to 70-78% by experts’ agreement. Conclusion: These guidelines were completed throughout systematic reviews and evaluations by clinical experts. Their contents are also included about overall managements for PIV therapy. Therefore these guidelines could help PIV practitioners to make evidence based decision. Relevance to clinical practice: The method and result of this study are described specifically in figures, tables and appendix, which could give guidance to nurses who develop guidelines regarding other subjects.